Доверься врагу: [роман] / Сергей Самаров - Самаров Сергей Васильевич (Спецназ ГРУ, 2010)
Экземпляры: ф.12 (20151009) / Инвентарный номер: 60186 / Цена: 50.00 / Авт.знак: С 17 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-44